Matt antifouling and wear-resistant glaze, ceramic tile and preparation method thereof

By using raw materials such as high aluminum alum soil, oxidation, silicate, and molten molten melting powder in ceramic glaze, build ZNO-AL2O3-SIO2 systems, solving ceramic glaze is difficult to matte, anti-pollution-proof, anti-dirt prevention The problem of abrasion resistance and high light transparency realizes the high wear resistance, anti -dirt resistance and good light transmittability of the glaze, while maintaining a good hair color effect.

CN119038878BActive Publication Date: 2025-01-28GUANGDONG XINRUNCHENG CERAMICS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411535626.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-28
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

Existing ceramic glazes are difficult to have both matte, stain-proof, wear-resistant and high light-transmitting properties, and affect the color effect of the glaze.

Method used

Using raw materials such as high aluminum alum soil, oxidation, silicate, and molten molten melting powder, build ZNO-Al2O3-SIO2 systems to form a state of coexistence of oxidation, silicate and oxide chloride polycrystalline, combined with combining Basic glaze such as potassium long stones and air knives, optimize silicon aluminum ratios, and prepare matte pollution -resistant wear -resistant glaze.

Benefits of technology

The hardness of the glazed Mo's hardness reaches level 7.5 or more, the abrasion resistance can reach 15,000 rpm, the anti -pollution is 5 levels, and the light transmission can reach more than 70%. At the same time, it maintains a good hair color effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of building ceramics, and specifically discloses a matte anti-fouling and wear-resistant glaze, a ceramic tile and a preparation method thereof. The raw material components of the matte anti-fouling and wear-resistant glaze include, by weight: 5-10 parts of high-alumina bauxite; 3-8 parts of calcined sillimanite; 30-35 parts of potassium feldspar; 6-12 parts of air knife clay; 10-15 parts of zinc oxide; 5-10 parts of quartz sand; 4-8 parts of zirconium oxide; 4-8 parts of zirconium silicate; 10-15 parts of zirconium-containing matte frit powder; wherein: Al in high-alumina bauxite is 10-15 parts of zirconium oxide; 2 O 3 The content of is higher than 75%, the maximum particle size of quartz sand is no more than 10 μm, and the zirconium source in the zirconium-containing matte frit powder is zirconium oxychloride. The present invention prepares a matte anti-fouling and wear-resistant glaze by optimizing and reasonably compounding the raw materials, achieving a glaze surface Mohs hardness of more than 7.5, wear resistance of 5 levels at 15,000 revolutions, anti-fouling level 5, and a glaze layer visible light transmittance of more than 70%, with good coloring effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building ceramics, and in particular relates to a matte anti-fouling and wear-resistant glaze, a ceramic tile and a preparation method thereof. Background Art

[0002] Matt glaze is a glaze with less gloss and less reflective surface, and the glaze surface presents a matte or semi-matte effect. Although matte glaze does not have the eye-catching brightness of high-gloss glaze, its natural effect is close to that of natural materials, showing delicate and moist, without strong reflection, giving people a soft, quiet and comfortable visual experience. The unique "frosted feeling" of the matte surface alleviates the diffuse reflection formed by light, without dizziness or glare, and is kind to the eyes, so it is very popular among consumers.

[0003] However, the antifouling performance of the glaze surface is closely related to the glossiness of the surface. Generally speaking, the lower the glossiness, the higher the surface roughness, the lower the fineness of the glaze, and the antifouling performance also decreases. At the same time, most of the current industry controls the glossiness by lowering the melting temperature of the glaze to achieve the required matte range, but this method will reduce the wear resistance of the glaze. In order to improve the wear resistance of the glaze, it is mainly through the precipitation of crystals with high hardness in the glaze melt or the direct addition of high hardness raw materials, such as zirconium oxide, zircon sand, zirconium-containing silicate, etc., to improve the wear resistance of the product, but most of these raw materials are opacifying whitening agents, and the introduction of a large amount will lead to a decrease in the light transmittance of the glaze layer, affect the color of the glaze, and is not conducive to the reduction of glossiness. At the same time, matte and light transmittance are also a pair of contradictory properties. Generally speaking, the lower the glossiness, the worse the light transmittance. Therefore, the existing ceramic glazes cannot have matte, high antifouling, high wear resistance and high light transmittance at the same time.

[0004] Therefore, there is an urgent need to develop a ceramic glaze that can achieve high hardness, high wear resistance, and good light transmittance while ensuring a matte glaze surface, and will not affect the color effect of the product. Summary of the invention

[0005] The present invention provides a matte anti-fouling and wear-resistant glaze, a ceramic tile and a preparation method thereof, so as to solve one or more technical problems existing in the prior art and at least provide a beneficial choice or create conditions.

[0006] In order to solve the above technical problems, the first aspect of the present invention provides a matte anti-fouling and wear-resistant glaze, the raw material components of which include, by weight:

[0007] 5-10 parts of high alumina;

[0008] 3-8 parts of calcined sillimanite;

[0009] Potassium feldspar 30-35 parts;

[0010] 6-12 parts of air knife soil;

[0011] Zinc oxide 10-15 parts;

[0012] 5-10 parts of quartz sand;

[0013] 4-8 parts of zirconium oxide;

[0014] 4-8 parts of zirconium silicate;

[0015] 10-15 parts of zirconium-containing matte frit powder;

[0016] The content of Al2O3 in the high-alumina bauxite is higher than 75%, the maximum particle size of the quartz sand does not exceed 10 μm, and the zirconium source in the zirconium-containing matte frit powder is zirconium oxychloride.

[0017] The present invention selects a high-aluminum glaze system, with zirconium oxide, zirconium silicate and zirconium-containing matte frit powder with high wear resistance as main raw materials, so that zirconium oxide, zirconium silicate and zirconium oxychloride polycrystals coexist in the glaze melt; and constructs a ZnO-Al2O3-SiO2 system with zinc oxide, high-alumina bauxite, calcined sillimanite and quartz sand to promote the precipitation of high-hardness zinc aluminate crystals; at the same time, it is supplemented with basic glazes such as potassium feldspar and air knife clay, and the silicon-aluminum ratio of the glaze is controlled within a suitable range by optimizing and reasonably compounding the raw materials, so as to prepare a matte anti-fouling and wear-resistant glaze, which can achieve high anti-fouling and high wear resistance while ensuring matte and light transmittance.

[0018] Specifically, the present invention selects a zirconium-containing matte frit, and simultaneously adds zirconium oxide and zirconium silicate to achieve high wear resistance of the glaze. Since the zirconium source in the zirconium-containing matte frit is zirconium oxychloride (Mohs hardness is 9.0), the solubility of zirconium oxychloride in the glass glaze melt is very low. A small amount of zirconium oxychloride melted in the glass glaze will form a zirconium-saturated uniform high-temperature transparent melt, which is beneficial to improving the light transmittance of the glaze on the one hand, and on the other hand, it can prevent the high-temperature melting of the added zirconium oxide and zirconium silicate, and form high-hardness zirconium oxychloride. At the same time, some zirconium ions in the zirconium-containing matte frit will form zirconium silicate crystals with silicon in the glaze melt during the glaze firing process. The precipitated zirconium silicate crystals will use the added zirconium silicate as a crystallization carrier, further promoting the precipitation of zirconium silicate crystals. In addition, in the high-aluminum glaze melt environment, the large amount of [AlO4] present in the glass network structure can limit Si 4+ The diffusion of zirconium oxide (ZrO2) with higher wear resistance (Mohs hardness of about 8.5) in the glass phase is inhibited to generate ZrSiO4 (Mohs hardness of 7-8), so that zirconium oxide and zirconium silicate can coexist. Therefore, zirconium oxide, zirconium silicate, zirconium oxychloride and other crystals with high wear resistance exist in the glaze melt of the present invention, thereby greatly improving the wear resistance of the glaze and ensuring the light transmittance of the glaze layer.

[0019] At the same time, the present invention constructs a ZnO-Al2O3-SiO2 system with zinc oxide, high-alumina bauxite, calcined sillimanite and quartz sand. Both high-alumina bauxite and calcined sillimanite have a high Al2O3 content. In this system, zinc silicate (Mohs hardness 5-5.5) is not easy to precipitate, and is replaced by zinc spinel (ZnAl2O4). The Mohs hardness of the ZnAl2O4 crystal is 7.5-8, thereby further improving the wear resistance of the glaze layer.

[0020] In addition, the study found that the reason why the glaze is not resistant to pollution is not only related to the pores on its surface, but also to the holes left by the volume effect of quartz during the crystal transformation. In view of this, the present invention reduces the surface tension of the glaze by increasing the amount of high-temperature flux potassium feldspar in the glaze to reduce the generation of glaze pores; on the other hand, it reduces the particle size of quartz sand and improves the melting performance of quartz, thereby effectively alleviating the volume effect caused by the crystal transformation of quartz sand, thereby improving the anti-fouling performance of the glaze.

[0021] In some embodiments of the present invention, the content of Al2O3 in the high-alumina bauxite is 75-80%. High-alumina bauxite can increase the aluminum content of the system and form corundum crystals and mullite crystals during high-temperature sintering, which is beneficial to improving the wear resistance of the glaze.

[0022] In some embodiments of the present invention, the maximum particle size of the quartz sand does not exceed 10 μm. Fine-grained quartz sand is easier to melt, thereby reducing the content of unmelted quartz, thereby reducing glaze defects caused by unmelted quartz and improving anti-fouling performance.

[0023] In some embodiments of the present invention, the chemical composition of the matte zirconium-containing frit powder includes, by weight percentage: SiO2 35-45%, Al2O3 25-35%, K2O 1-4%, Na2O 1-2%, CaO 10-20%, MgO 1-5%, ZnO 1-4%, ZrO2 5-10%. The present invention adjusts the chemical composition of the frit so that it falls in the zirconium silicate crystallization zone, laying a foundation for the precipitation of zirconium silicate crystals.

[0024] In some embodiments of the present invention, in the chemical composition of the matte zirconium-containing frit powder, the molar ratio of SiO2 to Al2O3 is (2-3): 1. The matte effect of the glaze surface is achieved by controlling the silicon-aluminum ratio of the glaze.

[0025] In some embodiments of the present invention, the chemical composition of the calcined sillimanite includes, by weight percentage: SiO2 30-45%, Al2O3 55-60%, K2O 0.1-0.3%, Na2O 0.1-0.5%, CaO 0.1-0.5%, MgO 0.1-0.4%, Fe2O3 0.5-0.8%, TiO2 0.1-0.5%. The main chemical components of sillimanite are Al2O3 and SiO2, which will be transformed into mullite at high temperature, which is beneficial to improve the wear resistance of the glaze.

[0026] In some embodiments of the present invention, the calcination temperature of the calcined sillimanite is 1300-1400° C. Sillimanite is prone to volume expansion during heating, which is not conducive to the quality of the glaze. By pre-treating the sillimanite with high temperature calcination, the adverse effects of volume expansion can be effectively eliminated.

[0027] The second aspect of the present invention provides a method for preparing the above-mentioned matte antifouling and wear-resistant glaze, comprising the following steps:

[0028] (1) mixing raw materials for preparing zirconium-containing matte frit powder, melting them at 1400-1500° C. for 8-10 hours, and then pouring them into water for quenching to obtain frit particles; and then crushing the frit particles to obtain zirconium-containing matte frit powder;

[0029] (2) The matte zirconium-containing frit powder is mixed with other raw materials for preparing a matte antifouling and wear-resistant glaze, and then wet-milled to obtain the matte antifouling and wear-resistant glaze.

[0030] In some embodiments of the present invention, the particle size of the matte zirconium-containing frit powder is 80-100 mesh. If the particle size of the frit powder is too small, it is easy to agglomerate, resulting in uneven glaze mixing; if the particle size of the frit powder is too large, the wet ball milling time will be increased due to the high hardness of the frit.

[0031] In some embodiments of the present invention, the fineness of the matte antifouling and wear-resistant glaze is 0.2-0.4wt% of the residue on a 325-mesh sieve.

[0032] A third aspect of the present invention provides a matte antifouling and wear-resistant ceramic tile, comprising a body and a matte antifouling and wear-resistant glaze layer arranged on the upper surface of the body, wherein the matte antifouling and wear-resistant glaze layer is fired from the above-mentioned matte antifouling and wear-resistant glaze.

[0033] In some embodiments of the present invention, the thickness ratio of the matte antifouling and wear-resistant glaze layer to the body is 0.015-0.02.

[0034] Research has found that a suitable ratio of glaze layer to body thickness is beneficial to improving the wear resistance of the glaze layer. The main reasons are: if the glaze layer is too thick, the actual compressive stress on the glaze surface will be reduced, and the wear resistance will decrease; if the glaze layer is relatively thinner, the compressive stress caused by the surface tempering will be greater, and the wear resistance will also be improved.

[0035] The fourth aspect of the present invention provides a method for preparing the above-mentioned matte antifouling and wear-resistant ceramic tile, comprising the following steps:

[0036] The matte antifouling and wear-resistant glaze is applied to the green body to form a matte antifouling and wear-resistant glaze layer, and after drying and firing, the matte antifouling and wear-resistant ceramic tile is obtained.

[0037] In some embodiments of the present invention, the firing temperature regime is: first increase the temperature to 1150-1200°C at a heating rate of 10-15°C / min, and keep warm for 10-15 minutes; then cool down to 650-700°C at a rate of 20-25°C / min, and then cool down to 550-600°C at a rate of 5-10°C / min, and finally cool naturally after leaving the kiln.

[0038] Specifically, quartz will undergo a rapid crystal transformation from β-quartz to α-quartz at 573°C, and the quartz grains will be separated from the surrounding glass phase, resulting in glaze defects, thereby affecting the anti-fouling performance of the glaze. The present invention can greatly reduce the harm caused by the crystal transformation of quartz by adjusting the cooling system during the firing process and slowing down the cooling rate near the temperature of the crystal transformation from β-quartz to α-quartz, thereby improving the anti-fouling performance of the glaze.

[0039] In some embodiments of the present invention, the method for preparing the matte antifouling and wear-resistant ceramic tile comprises the following steps:

[0040] First, a base glaze is applied to the body, then a decorative pattern is inkjet printed, and then the matte antifouling and wear-resistant glaze is applied to form a base glaze layer, an inkjet printed pattern layer and a matte antifouling and wear-resistant glaze layer respectively. After drying and firing, the matte antifouling and wear-resistant ceramic tile is obtained.

[0041] Compared with the prior art, the above technical solution of the present invention has at least the following technical effects or advantages:

[0042] The present invention adopts a semi-melt high-aluminum matte glaze system, with zirconium oxide, zirconium silicate and zirconium-containing matte frit powder (zirconium source is zirconium oxychloride) with high wear resistance as main raw materials, so that zirconium oxide, zirconium silicate and zirconium oxychloride polycrystals coexist in the glaze melt; and constructs a ZnO-Al2O3-SiO2 system with zinc oxide, high-aluminum bauxite, calcined sillimanite and quartz sand to promote the precipitation of high-hardness ZnAl2O4 crystals; at the same time, by increasing the amount of high-temperature flux potassium feldspar in the glaze and reducing the particle size of quartz sand, while reducing the surface tension of the glaze, the crystal transformation of the quartz sand is alleviated, thereby effectively improving the anti-fouling performance of the glaze.

[0043] The present invention prepares a matte anti-fouling and wear-resistant glaze by optimizing and reasonably compounding various raw materials and controlling the silicon-aluminum ratio of the glaze within a suitable range. When the glaze is applied to ceramic tiles, the glaze surface can have a Mohs hardness of more than 7.5, a wear resistance of up to level 5 for 15,000 revolutions, an anti-fouling level of 5, a visible light transmittance of more than 70% and a good coloring effect. DETAILED DESCRIPTION

[0044] The present invention is described in detail below in conjunction with the examples, so that the technical personnel of the relevant technical field can understand the present invention. It is necessary to point out here that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. The non-essential improvements and adjustments made to the present invention by the skilled person in the relevant field according to the above invention content should still belong to the scope of protection of the present invention. At the same time, the raw materials mentioned below that are not described in detail are all commercially available products; the process steps or preparation methods that are not mentioned in detail are all process steps or preparation methods known to those skilled in the art.

[0045] The raw material components of the green body used in the examples and comparative examples of the present invention include, by weight: 5 parts of bentonite, 35 parts of clay, 50 parts of medium-temperature sand, 7 parts of high-temperature sand, and 3 parts of talc.

[0046] The raw material components of the bottom glaze layer include, by weight: 15 parts of nepheline, 30 parts of potassium feldspar, 5 parts of sodium feldspar, 15 parts of quartz, 8 parts of kaolin, 10 parts of burned kaolin, 15 parts of aluminum oxide, and 10 parts of zirconium silicate.

[0047] Example 1

[0048] A matte antifouling and wear-resistant glaze, the raw material components of which are measured by weight:

[0049] 5 parts of high alumina;

[0050] 3 parts of calcined sillimanite;

[0051] Potassium feldspar 30 parts;

[0052] 6 parts of air knife soil;

[0053] Zinc oxide 10 parts;

[0054] 5 parts of quartz sand;

[0055] 4 parts of zirconium oxide;

[0056] 4 parts of zirconium silicate;

[0057] 10 parts of zirconium-containing matte frit powder.

[0058] Wherein: the chemical composition of the zirconium-containing matte frit powder includes by weight percentage: SiO2 40%, Al2O3 30%, K2O2%, Na2O 2%, CaO 15%, MgO 4%, ZnO 2%, ZrO 25%; the zirconium source is zirconium oxychloride.

[0059] The chemical composition of the calcined sillimanite includes, by weight percentage: SiO2 40.5%, Al2O3 57.8%, K2O 0.2%, Na2O 0.2%, CaO 0.3%, MgO 0.2%, Fe2O3 0.6%, TiO2 0.2%. The calcination temperature of the calcined sillimanite is 1350°C.

[0060] The Al2O3 content in high-alumina bauxite is 76%, and the maximum particle size of quartz sand does not exceed 10μm.

[0061] A method for preparing a matte anti-fouling and wear-resistant ceramic tile comprises the following steps:

[0062] (1) According to the raw material ratio, the raw materials for preparing the zirconium-containing matte frit powder are mixed, melted at 1450° C. for 9 hours, poured into water and quenched to obtain frit particles; and then the frit particles are crushed to obtain the zirconium-containing matte frit powder with a fineness of 100 mesh;

[0063] (2) mixing the zirconium-containing matte frit powder obtained in step (1) with other raw materials for preparing matte antifouling and wear-resistant glaze according to the raw material ratio, adding water for ball milling (the mass ratio of material to water is 100:40), and obtaining a matte antifouling and wear-resistant glaze with a fineness of 0.3 wt% of 325 mesh residue;

[0064] (3) After mixing the raw materials of the base glaze layer according to the proportion, water is added for ball milling (the mass ratio of the material to water is 100:40), and the base glaze with a fineness of 0.3wt% of the residue on a 325-mesh sieve is obtained;

[0065] (4) Apply the base glaze and inkjet-printed decorative pattern obtained in step (3) on the green body, and then apply the matte antifouling and wear-resistant glaze obtained in step (2) to form a base glaze layer, an inkjet-printed pattern layer and a matte antifouling and wear-resistant glaze layer (the thickness ratio of the matte antifouling and wear-resistant glaze layer to the green body is 0.018). After drying and firing, the matte antifouling and wear-resistant ceramic tile of this embodiment is obtained.

[0066] The firing temperature regime is as follows: first increase the temperature to 1160°C at a rate of 12°C / min and keep warm for 10 minutes; then cool down to 650°C at a rate of 20°C / min, and then cool down to 573°C at a rate of 5°C / min, and finally cool naturally after leaving the kiln.

[0067] Example 2

[0068] A matte antifouling and wear-resistant glaze, the raw material components of which are measured by weight:

[0069] 10 parts of high alumina;

[0070] 8 parts of calcined sillimanite;

[0071] Potassium feldspar 35 parts;

[0072] 12 parts of air knife soil;

[0073] Zinc oxide 15 parts;

[0074] 10 parts of quartz sand;

[0075] 8 parts of zirconium oxide;

[0076] 8 parts of zirconium silicate;

[0077] 15 parts of zirconium matte frit powder.

[0078] Wherein: the chemical composition of the zirconium-containing matte frit powder includes by weight percentage: SiO2 35%, Al2O3 30%, K2O2%, Na2O 2%, CaO 18%, MgO 2%, ZnO 3%, ZrO 28%; the zirconium source is zirconium oxychloride.

[0079] The chemical composition of the calcined sillimanite includes, by weight percentage: SiO2 38.6%, Al2O3 59.7%, K2O 0.1%, Na2O 0.3%, CaO 0.2%, MgO 0.3%, Fe2O3 0.5%, TiO2 0.3%. The calcination temperature of the calcined sillimanite is 1350°C.

[0080] The Al2O3 content in high alumina is 80%, and the maximum particle size of quartz sand does not exceed 10μm.

[0081] A method for preparing a matte anti-fouling and wear-resistant ceramic tile comprises the following steps:

[0082] (1) According to the raw material ratio, the raw materials for preparing the zirconium-containing matte frit powder are mixed, melted at 1400° C. for 10 hours, poured into water and quenched to obtain frit particles; and then the frit particles are crushed to obtain the zirconium-containing matte frit powder with a fineness of 100 mesh;

[0083] (2) mixing the zirconium-containing matte frit powder obtained in step (1) with other raw materials for preparing matte antifouling and wear-resistant glaze according to the raw material ratio, adding water for ball milling (the mass ratio of material to water is 100:40), and obtaining a matte antifouling and wear-resistant glaze with a fineness of 0.2 wt% of 325 mesh residue;

[0084] (3) After mixing the raw materials of the base glaze layer according to the proportion, water is added for ball milling (the mass ratio of the material to water is 100:40), and the base glaze with a fineness of 0.3wt% of the residue on a 325-mesh sieve is obtained;

[0085] (4) The base glaze and inkjet-printed decorative pattern prepared in step (3) are applied on the green body, and then the matte antifouling and wear-resistant glaze prepared in step (2) is applied to form a base glaze layer, an inkjet-printed pattern layer and a matte antifouling and wear-resistant glaze layer (the thickness ratio of the matte antifouling and wear-resistant glaze layer to the green body is 0.017). After drying and firing, the matte antifouling and wear-resistant ceramic tile of this embodiment is obtained.

[0086] The firing temperature regime is as follows: first increase the temperature to 1180°C at a rate of 15°C / min and keep warm for 15 minutes; then cool down to 700°C at a rate of 25°C / min, and then cool down to 600°C at a rate of 10°C / min, and finally cool naturally after leaving the kiln.

[0087] Example 3

[0088] A matte antifouling and wear-resistant glaze, the raw material components of which are measured by weight:

[0089] 8 parts of high alumina;

[0090] 5 parts of calcined sillimanite;

[0091] Potassium feldspar 32 parts;

[0092] 10 parts of air knife soil;

[0093] Zinc oxide 12 parts;

[0094] 8 parts of quartz sand;

[0095] 6 parts of zirconium oxide;

[0096] 6 parts of zirconium silicate;

[0097] 12 parts of zirconium matte frit powder.

[0098] Among them: the chemical composition of the zirconium-containing matte frit powder includes, by weight percentage: SiO2 36%, Al2O3 28%, K2O 3%, Na2O 1%, CaO 15%, MgO 3%, ZnO 4%, ZrO2 10%; the zirconium source is zirconium oxychloride.

[0099] The chemical composition of the calcined sillimanite includes, by weight percentage: SiO2 38.7%, Al2O3 59.8%, K2O 0.2%, Na2O 0.2%, CaO 0.2%, MgO 0.3%, Fe2O3 0.5%, TiO2 0.1%. The calcination temperature of the calcined sillimanite is 1350°C.

[0100] The Al2O3 content in high-alumina bauxite is 78%, and the maximum particle size of quartz sand does not exceed 10μm.

[0101] A method for preparing a matte anti-fouling and wear-resistant ceramic tile comprises the following steps:

[0102] (1) According to the raw material ratio, the raw materials for preparing the zirconium-containing matte frit powder are mixed, melted at 1400° C. for 8 hours, poured into water and quenched to obtain frit particles; and then the frit particles are crushed to obtain the zirconium-containing matte frit powder with a fineness of 100 mesh;

[0103] (2) mixing the zirconium-containing matte frit powder obtained in step (1) with other raw materials for preparing matte antifouling and wear-resistant glaze according to the raw material ratio, adding water for ball milling (the mass ratio of material to water is 100:40), and obtaining a matte antifouling and wear-resistant glaze with a fineness of 0.4 wt% of 325 mesh residue;

[0104] (3) After mixing the raw materials of the base glaze layer according to the proportion, water is added for ball milling (the mass ratio of the material to water is 100:40), and the base glaze with a fineness of 0.4wt% of the residue on a 325-mesh sieve is obtained;

[0105] (4) The base glaze and inkjet-printed decorative pattern prepared in step (3) are applied on the green body, and then the matte antifouling and wear-resistant glaze prepared in step (2) is applied to form a base glaze layer, an inkjet-printed pattern layer and a matte antifouling and wear-resistant glaze layer (the thickness ratio of the matte antifouling and wear-resistant glaze layer to the green body is 0.019). After drying and firing, the matte antifouling and wear-resistant ceramic tile of this embodiment is obtained.

[0106] The firing temperature regime is as follows: first increase the temperature to 1170°C at a rate of 12°C / min and keep warm for 12 minutes; then cool down to 650°C at a rate of 20°C / min, and then cool down to 573°C at a rate of 8°C / min, and finally cool naturally after leaving the kiln.

[0107] Example 4

[0108] A matte antifouling and wear-resistant glaze, the raw material components of which are measured by weight:

[0109] 6 parts of high alumina;

[0110] 6 parts of calcined sillimanite;

[0111] Potassium feldspar 34 parts;

[0112] 8 parts of air knife soil;

[0113] Zinc oxide 14 parts;

[0114] 6 parts of quartz sand;

[0115] Zirconium oxide 5 parts;

[0116] 5 parts of zirconium silicate;

[0117] 14 parts of zirconium-containing matte frit powder.

[0118] Among them: the chemical composition of the zirconium-containing matte frit powder includes, by weight percentage: SiO2 42%, Al2O3 26%, K2O2%, Na2O 2%, CaO 12%, MgO 5%, ZnO 2%, ZrO 29%; the zirconium source is zirconium oxychloride.

[0119] The chemical composition of the calcined sillimanite includes, by weight percentage: SiO2 42.3%, Al2O3 56.0%, K2O 0.3%, Na2O 0.2%, CaO 0.4%, MgO 0.2%, Fe2O3 0.5%, TiO2 0.1%. The calcination temperature of the calcined sillimanite is 1350°C.

[0120] The Al2O3 content in high-alumina bauxite is 76%, and the maximum particle size of quartz sand does not exceed 10μm.

[0121] A method for preparing a matte anti-fouling and wear-resistant ceramic tile comprises the following steps:

[0122] (1) According to the raw material ratio, the raw materials for preparing the zirconium-containing matte frit powder are mixed, melted at 1450° C. for 9 hours, poured into water and quenched to obtain frit particles; and then the frit particles are crushed to obtain the zirconium-containing matte frit powder with a fineness of 100 mesh;

[0123] (2) mixing the zirconium-containing matte frit powder obtained in step (1) with other raw materials for preparing matte antifouling and wear-resistant glaze according to the raw material ratio, adding water for ball milling (the mass ratio of material to water is 100:40), and obtaining a matte antifouling and wear-resistant glaze with a fineness of 0.3 wt% of 325 mesh residue;

[0124] (3) After mixing the raw materials of the base glaze layer according to the proportion, water is added for ball milling (the mass ratio of the material to water is 100:40), and the base glaze with a fineness of 0.3wt% of the residue on a 325-mesh sieve is obtained;

[0125] (4) Apply the base glaze and inkjet-printed decorative pattern obtained in step (3) on the green body, and then apply the matte antifouling and wear-resistant glaze obtained in step (2) to form a base glaze layer, an inkjet-printed pattern layer and a matte antifouling and wear-resistant glaze layer (the thickness ratio of the matte antifouling and wear-resistant glaze layer to the green body is 0.018). After drying and firing, the matte antifouling and wear-resistant ceramic tile of this embodiment is obtained.

[0126] The firing temperature regime is as follows: first increase the temperature to 1200°C at a rate of 12°C / min and keep warm for 15 minutes; then cool down to 700°C at a rate of 20°C / min, and then cool down to 550°C at a rate of 5°C / min, and finally cool naturally after leaving the kiln.

[0127] Comparative Example 1

[0128] The only difference between Comparative Example 1 and Example 1 is that the raw material components of the matte antifouling and wear-resistant glaze of Comparative Example 1 use an equal amount of ordinary bauxite (aluminum content of 45%, 13 parts by weight) to replace the high-alumina bauxite and sillimanite in Example 1.

[0129] Comparative Example 2

[0130] The difference between Comparative Example 2 and Example 1 is that zinc oxide is not added to the raw material components of the matte antifouling and wear-resistant glaze of Comparative Example 2.

[0131] Comparative Example 3

[0132] The only difference between Comparative Example 3 and Example 1 is that zirconium oxide is not added to the raw material components of the matte antifouling and wear-resistant glaze of Comparative Example 3.

[0133] Comparative Example 4

[0134] The only difference between Comparative Example 4 and Example 1 is that the zirconium source in the zirconium-containing matte frit powder in the raw material components of the matte antifouling and wear-resistant glaze of Comparative Example 4 is zirconium silicate.

[0135] Comparative Example 5

[0136] The only difference between Comparative Example 5 and Example 1 is that the average particle size of the quartz sand in the raw material components of the matte antifouling and wear-resistant glaze of Comparative Example 5 is 30 μm.

[0137] Comparative Example 6

[0138] The only difference between Comparative Example 6 and Example 1 is that in the preparation method of the matte anti-fouling and wear-resistant ceramic tile in Comparative Example 6, the thickness ratio of the matte anti-fouling and wear-resistant glaze layer to the green body is 0.03.

[0139] Comparative Example 7

[0140] The only difference between Comparative Example 7 and Example 1 is that the preparation method of the matte antifouling and wear-resistant ceramic tiles in Comparative Example 7 adopts natural cooling.

[0141] Performance Testing

[0142] The matte anti-fouling and wear-resistant ceramic tile samples prepared in the above Examples 1-4 and Comparative Examples 1-7 were tested for Mohs hardness, wear resistance, anti-fouling, glossiness, and light transmittance performance of the matte anti-fouling and wear-resistant glaze layer. Among them: the wear resistance is tested according to GB / T3810.7-2016 "Determination of surface wear resistance of ceramic glazed tiles"; the anti-fouling performance is tested according to GBT 3810.14-2016 "Ceramic tile test method Part 14: Determination of pollution resistance"; the light transmittance is tested according to GB2680-2021 "Determination of visible light transmittance, direct sunlight transmittance, total solar energy transmittance, ultraviolet transmittance and related window glass parameters of architectural glass" to determine the visible light transmittance of the matte anti-fouling and wear-resistant glaze layer, and the test results are shown in Table 1.

[0143] Table 1: Performance comparison of samples obtained from Examples 1-4 and Comparative Examples 1-7

[0144]

[0145] It can be seen from Table 1 that the ceramic tile samples prepared in Examples 1-4 of the present invention have a glossiness of 10-15° and a matte gloss; the Mohs hardness can reach 7.5-8.0, the wear resistance can reach level 5 15,000 revolutions, and the anti-fouling level can reach level 5, with high wear resistance and high anti-fouling properties; and the visible light transmittance of the matte anti-fouling and wear-resistant glaze layer is more than 70%, and the color development performance is good.

[0146] In Comparative Example 1 relative to Example 1, since ordinary bauxite with lower aluminum content is used to replace high-alumina bauxite and sillimanite, zinc silicate and zirconium silicate will mainly precipitate in the glaze melt, and the contents of zinc spinel and zirconium oxide are greatly reduced, resulting in a significant decrease in the hardness and wear resistance of the product compared with Example 1.

[0147] Compared with Example 1, since zinc oxide and zirconium oxide were not added respectively, the contents of zinc spinel and zirconium oxide in the glaze layer decreased in Comparative Example 2-3, and the hardness and wear resistance of the product were not as good as those in Example 1.

[0148] In Comparative Example 4 relative to Example 1, since zirconium silicate is used as the zirconium source instead of zirconium oxychloride, the content of zirconium oxychloride in the glaze layer is reduced, and the hardness, wear resistance and light transmittance of the glaze layer are all reduced compared with Example 1.

[0149] Compared with Example 1, in Comparative Example 5, since the particle size of quartz sand is larger, the volume effect brought about by its crystal transformation causes the anti-fouling performance of the glaze to be significantly reduced compared with Example 1.

[0150] Compared with Example 1, since the thickness ratio of the matte anti-fouling and wear-resistant glaze layer to the body is increased, the actual compressive stress of the glaze surface is increased, and the compressive stress caused by the surface tempering effect is reduced. Therefore, the wear resistance is reduced compared with Example 1.

[0151] Compared with Example 1, in Comparative Example 7, due to the use of direct cooling, the rapid crystal transformation of β-quartz to α-quartz affects the anti-fouling performance of the glaze.

[0152] For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, without having to go through creative labor. Therefore, simple improvements made to the present invention by those skilled in the art based on the disclosure of the present invention should be within the protection scope of the present invention. The above embodiments are preferred embodiments of the present invention, and all processes similar to the present invention and equivalent changes made should belong to the protection scope of the present invention.

Claims

1. A matte antifouling and wear-resistant glaze, characterized in that: By weight, the raw material components include: 5-10 parts of high alumina; 3-8 parts of calcined sillimanite; Potassium feldspar 30-35 parts; 6-12 parts of air knife soil; Zinc oxide 10-15 parts; 5-10 parts of quartz sand; 4-8 parts of zirconium oxide; 4-8 parts of zirconium silicate; 10-15 parts of zirconium-containing matte frit powder; The content of Al2O3 in the high-alumina bauxite is higher than 75%, the maximum particle size of the quartz sand does not exceed 10 μm, and the zirconium source in the zirconium-containing matte frit powder is zirconium oxychloride.

2. The matte antifouling and wear-resistant glaze according to claim 1, characterized in that: The chemical composition of the zirconium-containing matte frit powder includes, by weight percentage, 35-45% SiO2, 25-35% Al2O3, 1-4% K2O, 1-2% Na2O, 10-20% CaO, 1-5% MgO, 1-4% ZnO, and 5-10% ZrO2.

3. The matte antifouling and wear-resistant glaze according to claim 2, characterized in that: In the chemical composition of the zirconium-containing matte frit powder, the molar ratio of SiO2 to Al2O3 is (2-3):

1.

4. The matte antifouling and wear-resistant glaze according to claim 1, characterized in that: The chemical composition of the calcined sillimanite includes, by weight percentage, 30-42.3% SiO2, 55-60% Al2O3, 0.1-0.3% K2O, 0.1-0.5% Na2O, 0.1-0.5% CaO, 0.1-0.4% MgO, 0.5-0.8% Fe2O3 and 0.1-0.5% TiO2.

5. The matte antifouling and wear-resistant glaze according to claim 1 or 4, characterized in that: The calcination temperature of the calcined sillimanite is 1300-1400°C.

6. A method for preparing a matte antifouling and wear-resistant glaze, characterized in that: The preparation method is used to prepare the matte antifouling and wear-resistant glaze according to any one of claims 1 to 5, comprising the following steps: (1) mixing raw materials for preparing zirconium-containing matte frit powder, melting them at 1400-1500° C. for 8-10 hours, and then pouring them into water for quenching to obtain frit particles; and then crushing the frit particles to obtain zirconium-containing matte frit powder; (2) The matte zirconium-containing frit powder is mixed with other raw materials for preparing a matte antifouling and wear-resistant glaze, and then wet-milled to obtain the matte antifouling and wear-resistant glaze.

7. A matte anti-fouling and wear-resistant ceramic tile, characterized in that: It comprises a body and a matte antifouling and wear-resistant glaze layer arranged on the upper surface of the body, wherein the matte antifouling and wear-resistant glaze layer is fired from the matte antifouling and wear-resistant glaze according to any one of claims 1 to 5.

8. The matte antifouling and wear-resistant ceramic tile according to claim 7, characterized in that: The thickness ratio of the matte antifouling and wear-resistant glaze layer to the body is 0.015-0.

02.

9. A method for preparing a matte antifouling and wear-resistant ceramic tile, characterized in that: The preparation method is used to prepare the matte anti-fouling and wear-resistant ceramic tile according to claim 7 or 8, comprising the following steps: The matte antifouling and wear-resistant glaze is applied to the green body to form a matte antifouling and wear-resistant glaze layer, and after drying and firing, the matte antifouling and wear-resistant ceramic tile is obtained.

10. The method for preparing the matte antifouling and wear-resistant ceramic tile according to claim 9, characterized in that: The firing temperature system is: firstly increase the temperature to 1150-1200°C at a heating rate of 10-15°C / min, keep the temperature for 10-15min; then cool down to 650-700°C at a rate of 20-25°C / min, then cool down to 550-600°C at a rate of 5-10°C / min, and finally cool naturally after leaving the kiln.

Citation Information

Patent Citations

  • Wear-resistant digital ceramic glaze

    CN113896421A

  • Velvet glaze, velvet ceramic tile and preparation method of velvet ceramic tile

    CN117865484A